Drill Method to Improve Students' Knowledge in the Course of Nursing Philosophy and Theories - Meinarisa Meinarisa; Riska Amalya Nasution; Indah Mawarti; Putri Irwanti Sari; Rina Oktaria (Indonesian Journal of Global Health Research, 2024)
Critical thinking in the concept of nursing philosophy in nursing is complex and is explained by various different definitions. These various definitions have caused confusion about what is meant by understanding the concept or model of nursing. Many literature reviews have examined nursing model theories and related definitions and measurements, but none offer a new perspective to view the same conclusion. The researcher looked at the use of the drilling method drill method to improve students' knowledge in the course of nursing philosophy and theoriesin. The research design used a pre-test and post-test without a control group, which is a design that treats one group without a comparison group. Respondents numbered 120 students who were members of the nursing theory class which were then divided into 4 large groups. The effectiveness of the treatment was assessed by comparing the post-test and pre-test scores. During this study, respondents will be given 6 learning sessions divided into 12 face-to-face meetings related to nursing theory, namely the theories of Florence Nightingale, Jean Orlando, Martha E Roger, and Watson. The results of the statistical test using the Wilcoxon test obtained a p value = 0.001, there was a significant difference in knowledge between before and after being given the Drilling Method. The knowledge of respondents after being given the Drilling Method showed a significant increase, so it is important to continue using the Drilling Method to improve knowledge and competence. The Drilling Method is an effective learning method to improve competence in the cognitive aspect. In the future, this method is expected to be applied in the learning process to improve the competence of nursing students in other courses.